Proposed interior design scheme of Anjung Singgah Perak Branch for Yayasan Kebajikan Negara (YKN), at NO.3, Jalan Sultan Azlan Shah, 31400 Ipoh, Perak Darul Ridzuan / Ainur Syuhada Arippin - Arippin, Ainur Syuhada (Faculty of Architecture, Planning and Surveying, 2011)
The project that had been chosen for this final project is Proposed Interior Scheme of Anjung Singgah Perak Branch For Yayasan Kebajikan Negara (YKN) at No.3, Jalan Sultan Azlan Shah, 31400 Ipoh, Perak Darul Ridzuan. The Anjung Singgah is a research centre to prevent the homeless issues. Before this, the Anjung Singgah was known as “Pusat Sehenti Intervensi Bagi Menangani Isu Gelandangan”. The Anjung Singgah is also a shelter for the homeless people that offers them get a better chance to survive independantly. The purpose of this project is to open a new branch of Anjung Singgah at Perak based on the identity of the Anjung Singgah its own. The focus of this project is to solve the issues and to accomplish all the objectives of this project in order to fulfill all the requirqment from the client. This project is also related with the instinct of Anjung Singgah which want to open other branch in other state as the main office is at Kuala Lumpur. Besides, this opening of the new branch will encourage the humanity feeling among the society especially in young generation. Furthermore, it is also will reduce the number of the homeless people in this country and increase the number of productivity among the community.